Neonatal hearing screening in Soba University Hospital, Khartoum, Sudan: a cross-sectional study - Siddig E. Kardman; Elham M. Omer; Nagat Abdalla; Osama Mohamed Khalid Edris; Abdelmoneim E. M. Kheir (The Egyptian Journal of Otolaryngology, 2023)
Abstract Background Hearing loss in children constitutes a serious obstacle to their optimal development; early detection of hearing disability is vital to improve the outcome of management; currently, in Sudan, there is no national neonatal hearing screening program. The aim of this study is to discuss the results of neonatal hearing screening among newborns admitted to neonatal intensive care unit (NICU) and well-baby nursery, at Soba University Hospital, Khartoum (Sudan), and to reflect the magnitude of risk factors for hearing impairment present in these two different groups of newborns. Methods In this hospital-based cross-sectional study, newborns who were admitted to the NICU or being observed in the well-baby nursery in the period from February 2014 to February 2019 were screened for hearing loss using automated otoacoustic emission (OAE) device after recording the risk factors for hearing loss according to the Joint Committee on Infant Hearing (JCIH) year 2007 position statement and after conducting a detailed ear and general physical examination. Newborns who failed this screening test were rescreened using the same device after 48 h, and if they failed again, they underwent confirmatory auditory brainstem response test when they are 6 months old. Results One thousand one hundred twenty newborns were tested; 736 were NICU and 384 were well-baby nursery newborns. The prevalence of hearing impairment after confirmatory test was found to be 10.8 per 1000 in the NICU group and 5.2 per 1000 in the well-baby nursery group considering that the drop rate for the confirmatory test was 50% and 66% respectively which is very high and reflect the poor compliance to the program. The risk factors for hearing loss were more encountered in the NICU group compared to well-baby nursery group. Unmonitored ototoxic drug use was found to be very prevalent and need urgent reconsideration. Conclusion In this study, the estimated prevalence of neonatal hearing impairment is alarming; risk factors are very evident especially in the NICU group; this reflect the urgent need for establishing an efficient national program for neonatal hearing screening and working to eliminate the preventable risk factors for neonatal hearing impairment in this developing country.